Tooth spray with active ingredients casein phosphopeptide – amorphous calcium phosphate (CPP – ACP) and ethanolic extract propolis (EEP) to inhibit tooth demineralization - Sahlan, Muhamad; Purwanti, Lucia (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2016)
Dental caries is a disease caused by the microbial infection that produces localized damage to the tissue classification. The process begins by demineralization in hard tissue followed by damage to the organic material. Dental caries happens because of demineralization without balanced by remineralization. In this study, tooth powder spray and tooth liquid spray was made with active ingredients of 10% w/w CPP-ACP (Casein Phosphopeptide - Amorphous Calcium Phosphate) and EEP (Ethanolic Extract Propolis), with the variation of 0%, 2%, and 4% w/w EEP in each preparation to inhibit demineralization. Each preparation should pass organoleptic and viscosity study to maintain the quality. pH of each preparation was evaluated to ensure that each preparation has pH above the critical pH of the oral environment. The stability of polyphenol as the antibacterial agent was evaluated for a month to assure the bioavailability in the preparations. The result shows that each preparation has enough organoleptic aspect and proper viscosity. pH level in each preparation is stable above critical pH of mouth environment (5.5), it ranges between 6.5 – 7.12. Polyphenol content in each preparation is stable with highest polyphenol content in tooth powder spray of 4% EEP, i.e. 1.39 – 1.45% (w/w). Qualitative evaluation of tooth morphology by SEM shows that preparations can inhibit enamel demineralization relatively to negative control.